An error analysis on translation made by the sixth semester students of English Department of IKIP Gunungsitoli - Kristof Martin Efori Telaumbanua (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The Objective off this study are to describe (1) the kinds of error made by the 6th semester students of English Department when translating Indonesia text into English, (2) the dominant error made by students, 3) how students made the error when translating Indonesia text into English text. This study used the descriptive qualitative research. The subject of this research is the 6th semester students and the object in this research is all the errors on translation made by students. The data collected to answer all the research problems are all the errors made by students. Based on data analysis, the writer finds that 1) students made error in Omission, Addition, Mis-formation, and Mis-ordering errors, 2) students made more dominant error in Mis-formation error, 3) students made error by: a) omitting an item that must appear in well-formed utterance, b) adding an item that must not appear in well-formed utterance, c) using the incorrect morpheme or group or structure, d) doing the incorrect placement of a morpheme or group of morpheme. The conclusion of this study is, the students are lack of vocabulary when doing translation. It is suggestion to the students to enrich their vocabulary and to the lecturer to enrich their students’ vocabularies by giving them daily new vocabularies.